2006
DOI: 10.1038/nature04445
|View full text |Cite
|
Sign up to set email alerts
|

Localized maternal orthodenticle patterns anterior and posterior in the long germ wasp Nasonia

Abstract: The Bicoid (Bcd) gradient in Drosophila has long been a model for the action of a morphogen in establishing embryonic polarity. However, it is now clear that bcd is a unique feature of higher Diptera. An evolutionarily ancient gene, orthodenticle (otd), has a bcd-like role in the beetle Tribolium. Unlike the Bcd gradient, which arises by diffusion of protein from an anteriorly localized messenger RNA, the Tribolium Otd gradient forms by translational repression of otd mRNA by a posteriorly localized factor. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
194
2
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(208 citation statements)
references
References 26 publications
8
194
2
4
Order By: Relevance
“…This apparent paradox is resolved only when considering gene regulatory networks as a whole. The labs of Reinhard Schroeder, of the University of Tübingen, Germany, and Claude Desplan, of New York University, for example, found that several genes that are activated by Bicoid after fertilization in fruitflies are deposited into the egg before fertilization in the flour beetle 2 and a parasitic wasp 3 . The lack of Bicoid is compensated by minor changes in the action of several other genes in the developmental network.…”
Section: Beneath the Surfacementioning
confidence: 99%
“…This apparent paradox is resolved only when considering gene regulatory networks as a whole. The labs of Reinhard Schroeder, of the University of Tübingen, Germany, and Claude Desplan, of New York University, for example, found that several genes that are activated by Bicoid after fertilization in fruitflies are deposited into the egg before fertilization in the flour beetle 2 and a parasitic wasp 3 . The lack of Bicoid is compensated by minor changes in the action of several other genes in the developmental network.…”
Section: Beneath the Surfacementioning
confidence: 99%
“…In insects exhibiting long germ embryogenesis, however, head and thoracic segments are patterned further towards the anterior egg pole. It has been proposed that this spatial shift in anterior patterning required the evolution of an instructive anterior patterning gradient to complement the action of existing posterior determinants (Lynch et al 2006a). The localization of maternal mRNAs to the anterior pole of the oocyte is observed in T. castaneum, N. vitripennis and D. melanogaster (Lawrence 1992;Bucher et al 2005;Olesnicky & Desplan 2007); figure 1.…”
Section: Molecular Transitions Underlying the Evolution Of Long Germ mentioning
confidence: 99%
“…The mechanism by which maternal protein gradients form in N. vitripennis is slightly different from that of D. melanogaster-rather than proteins diffusing from localized sources of mRNA, on fertilization mRNAs are released from the egg pole and diffuse to form mRNA gradients that are converted into protein gradients via translation. The maternal Orthodenticle-1 gradient functions to activate anterior segmentation genes, such as the gap genes empty spiracles, (zygotic) giant and hunchback (Lynch et al 2006a), while the maternal Giant gradient functions to set the anterior expression boundary of the central gap gene Krüppel (Brent et al 2007). The repressive role of maternal Giant is permissive for anterior development, since, in its absence, Krü ppel expression spreads anteriorly to repress the anterior gap gene hunchback (Brent et al 2007).…”
Section: Molecular Transitions Underlying the Convergent Evolution Ofmentioning
confidence: 99%
See 2 more Smart Citations